PENINGKATAN PROFESIONALISME GURU MIN 4 PALANGKARAYA DALAM MENULIS PTK MELALUI APLIKASI HARZING PUBLISH OR PERISH - Pionera, Mutiarani; Elhawwa, Tazkiyatunnafs; Norcahyono, Norcahyono (STKIP Persada Khatulistiwa Sintang, 2022)
ABSTRACTCommunity service in increasing the professionalism teachers of MIN 4 Palangkaraya in writing CAR through the Harzing Publish or Perish application. The aim was improving the professional competence of teachers in integrating teaching with assisted development by using the Harzing Publish or Perish Application to write bibliography. Thus, the results of the implementation of CAR can produce learning innovations that will be in the form of reports and converted into CAR articles so that they are ready to be published in scientific journals. The end result of this activity is that teachers can understand the classroom action research methodology. This event will be held for 1 day on Thursday June 23 2022 by scheduling 2 sessions. In the first session with training materials with PTK by resource person Dr. Eko Supraptono, M.Pd. Continue with session II with material on the Harzing Publish or Perish application by resource person Dr. Adirasa Hadi Prasetyo, M.Pd.I. This is in line with the very good response and supports this activity, as evidenced by the average percentage of the questionnaire results of 78.85 %. So, in the evaluation of this activity, it is hoped that it can be held again and carry out activities for more than 1 day. In this activity 2 articles were produced and ready to be published in related journals. Keywords: competency improvement, teacher professionalism, and written works.Â ABSTRAKPengabdian masyarakat ini berjudul peningkatan profesionalisme Guru MIN 4 Palangkaraya dalam menulis PTK melalui aplikasi Harzing Publish or Perish. Bertujuan untuk meningkatkan kompetensi profesional guru dalam mengintegrasikan pengajaran dengan pengembangan yang dibantu dengan menggunakan Aplikasi Harzing Publish or Perish untuk menuliskan daftar Pustaka. Sehingga, hasil pelaksanaan PTK dapat menghasilkan inovasi pembelajaran akan di tulis berupa laporan dan diubah menjadi artikel PTK sehingga siap di publikasikan pada jurnal ilmiah. Hasil akhir dari kegiatan ini adalah guru-guru dapat memahami metodologi penelitian tindakan kelas. kegiatan pelatihan ini dilaksanakan selama 1 hari yaitu pada Hari Kamis tanggal 23 Juni 2022 dengan menjadwalkan 2 sesi. Pada sesi pertama dengan materi pelatihan dengan PTK oleh narasumber Dr. Eko Supraptono, M.Pd. Di lanjutkan dengan sesi II dengan materi aplikasi Harzing Publish or Perish oleh narasumber Dr. Adirasa Hadi Prasetyo, M.Pd.I. Hal ini sejalan dengan respon sangat baik dan mendukung kegiatan ini, dibuktikan dengan rata-rata presentase hasil kuesioner sebesar 78.85 %. Sehingga, dalam evaluasi pada kegiatan ini diharapkan dapat tetap terselenggara kembali dan melaksanakan kegiatan lebih dari 1 hari. Pada kegiatan ini di hasilkan 2 artikel dan siap di publikasikan pada jurnal terkait.Kata kunci: peningkatan kompetensi, profesionalisme guru, dan karya tulis.